Use of GeoGebra in problem-solving in the field of Mathematics - Guanochanga Llerena , Katty Soraya; Casaliglla Ger, Darwin Fabricio (SATHIRI, 2025)
The research addressed the teaching and learning of mathematics in primary education, with a particular focus on problem-solving, identified as a difficulty for students. The objective was to propose the use of GeoGebra as a didactic resource to address this difficulty in fourth-grade students of Basic General Education at the Bolívar Educational Unit in Tulcán. The methodology included a mixed approach of quasi-experimental design of the pre-experimental type, with a pretest-posttest design in three groups, without a control group. Interviews with teachers and surveys of students were conducted to understand their perspectives and prior skills with GeoGebra. Pretests and posttest were carried out, the first in conventional classes and the second, using GeoGebra; problem-solving was evaluated based on specific phases and metrics. Normality tests, one-way ANOVA, and N-Gain were calculated to determine the difference between groups. The results indicated that teachers see the need to use GeoGebra and that students have difficulties in problem-solving due to reasoning problems. Students expressed not having used GeoGebra, but showed interest in its use. The data were parametric, and there were no significant differences between groups. However, an improvement was observed between pretest and posttest scores, although no significant differences were found between phases and scores. In conclusion, the use of GeoGebra is shown as a positive resource for learning mathematics.
Keywords: GeoGebra; mathematics; gamification; problem-solving; primary education